Physical, Consumer, and Social Aspects of Measuring the Food Environment Among Diverse Low-Income Populations - Gittelsohn, Joel (2009)
Obesity and other diet-related chronic diseases are directly related to the food environment. We describe how to better assess the food environment in specific ethnic minority settings for designing and implementing interventions, based on a review of our previous work on the food environment in American Indian reservations, Canadian First Nations reserves, the Republic of the Marshall Islands, and inner-city Baltimore. The types of food stores available within each setting and the range of healthy foods available varied greatly across these geographic regions. In all settings, proximity to food stores/supermarkets, cost, and limited availability of healthful foods were common features, which limited access to health-promoting food options. Features specific to each population should be considered in an assessment of the food environment, including physical (e.g., openness of stores, mix of types of food sources); consumer (e.g., adequacy of the food supply, seasonal factors); and social (e.g., inter-household food sharing, perceptions of food quality, language differences) aspects. The food environments common in low-income ethnic subpopulations require special focus and consideration due to the vulnerability of the populations and to specific and unique aspects of each setting.